Are Currency Crises Predictable? - Valdes, Rodrigo; Goldfajn, Ilan. (Washington, D.C. : International Monetary Fund, 1997)
This paper studies whether exchange rate expectations and overvaluations are predictors of currency crises. The results suggest that overvaluation has predictive power in explaining crises. However, although expected depreciation obtained from survey data partially takes different measures of exchange rate misalignment into consideration, expectations fail to anticipate currency crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet